APPLYING WORD WALL BY STICKY NOTE: A PRACTICES OF MEDIA TO INVOLVE STUDENTS’ WRITING - Putri Novitasari (Pedagogic Research-Applied Literacy Journal, 2025)
The objective of this study was to find out whether there was significance impact of word wall for solving students’ problem in writing a descriptive text. By this research researcher applied word wall in form of making sticky note to guide the students to compose sentences about describing place. Quantitative research was implemented as the research design. The sample was 36 students from seventh grade of junior high school. The result of post test showed that the students’ mean score before learned using word wall was 69.2 and reached to 82.5 after the teacher invited them to use ward wall. The result of t-score was 14.92 and the t-table was 3.59. Furthermore, it can be summed up that there was significant effect between word wall and students’ writing.  The increasing of mean score proved that there was improvement on students’ writing in composing descriptive text by applying word wall in sticky notes as the  media for teaching and learning process.